HEMOSTASIS AND FUNCTIONAL PROPERTIES OF NEUTROPHILS IN PATIENTS WITH VARIOUS SENSITIVITY TO ACETYLSALICYLIC ACID IN ACUTE CORONARY SYNDROME - I. Yu. Grinshtein; А. А. Savchenko; Yu. I. Grinshtein; N. Yu. Shimokhina; М. М. Petrova (Кардиоваскулярная терапия и профилактика)
Aim. To study the specifics of relation between hemostasis parameters and functional activity of neutrophil granulocytes in sensitive and resistant to acetylsalicylic acid (ASA) patients with acute coronary syndrome.Material and methods. Totally 53 patients included during the first 24 hours of ACS. Controls consisted of 50 relatively healthy individuals. All patients before the treatment and revascularization were assessed for the resistance to ASA, and selected into groups of sensitive (AS) and resistant (AR). Sensitivity test was done in vitro. In all participants the coagulation and platelet clotting systems were studied. With the luminescent method the neutrophil activity was assessed. Results. In AR with ACS there was decrease of platelets in blood, decreased level of ADP- (ADP 5 mcM) and adrenalin-induced aggregation, increases the level of ADP-induced platelets aggregation (PA) with ADP 0,1 mcM, and von Willebrand factor level. In the ASA sensitive patients there was a decrease of adrenalin induced aggregation.There were no specifics of coagulation hemostasis according to ASA sensitivity. Chemiluminiscence (CL) of neutrophils in ACS has a maximized out time. In AR there was decrease of activation. In AS functional activity of neutrophils more significantly correlates with the parameters of clotting, but in AR — with fibrinolytic and anticoagulation parameters.Conclusion. In ACS patients depending on ASA sensitivity, there are character specifics of platelet clotting: increase of ADP-induced aggregation in AR, decrease of platelet amount and the level of von Willebrand factor. In ACS patients there is a decreased velocity of "respiratory boost" in neutrophils. In AR there is more prominent dysbalance of coagulation hemostasis and "respiratory boost" of neutrophils, with the decrease of neutrophil reactivity related to clotting activity and appearance of relations with the parameters of fibrinolytic and anticoagulation activity.